Utilization of Ferroconcrete and Steel Timber Hybridization Technique in Tall Structure using Analysis Tool Etabs - Dangi, Ram Raj Singh; Satbhaiya, Rahul (International Journal of Scientific Research in Civil Engineering, 2020)
As India is a developing nation thus settlement of large population need Multistorey structures. Lateral forces are considered as the forces assigning over a structure in horizontal direction which causes structure instability, deflection and failure. Seismic and wind load is considered as lateral forces.ETABS is an analysis tool which helps in structure modelling and designing as per standard specifications of preferred country.A hybrid system is a combination of two or more structural materials. Steel and concrete hybridization is the most common type of hybrid system. Steel structures are very common in the world because of its short duration of construction and high strength. To improve resistance and to overcome other limitations of individual steel structure it can be combined with other materials like hybrid systems.In this study, static analysis of 3-D building frames of G+7 storeys along with timber-steel hybrid structure with wire mesh (ferroconcrete) have been carried out.  ETAB software has been used for analysis purpose. Results are collected in terms of max. node displacements (resultant), max. moments, max. shear force, max. axial force, maximum storey drift.
Keywords: Hybrid; Composite Structure; Analysis; ETAB; Lateral Forces; Ferroconcrete